The American Heart Association Scientific Statement on salt sensitivity of blood pressure: Prompting consideration of alternative conceptual frameworks for the pathogenesis of salt sensitivity? - Kurtz, Theodore W; DiCarlo, Stephen E; Pravenec, Michal; Morris, R Curtis (Journal of hypertension, 2017)
: Recently, the American Heart Association (AHA) published a scientific statement on salt sensitivity of blood pressure which emphasized a decades old conceptual framework for the pathogenesis of this common disorder. Here we examine the extent to which the conceptual framework for salt sensitivity emphasized in the AHA Statement accommodates contemporary findings and views of the broader scientific community on the pathogenesis of salt sensitivity. In addition, we highlight alternative conceptual frameworks and important contemporary theories of salt sensitivity that are little discussed in the AHA Statement. We suggest that greater consideration of conceptual frameworks and theories for salt sensitivity beyond those emphasized in the AHA Statement may help to advance understanding of the pathogenesis of salt-induced increases in blood pressure and, in consequence, may lead to improved approaches to preventing and treating this common disorder.
Keywords: Sodium Chloride, Dietary; kuchyňská sůl; United States; Blood Pressure; Humans; Americká kardiologická asociace; krevní tlak; Spojené státy americké; Hypertension; lidé; American Heart Association; hypertenze